Evaluating Web-Based Care for Mental Health and Substance Use Issues for Lesbian, Gay, Bisexual, Transgender, Queer, Questioning, and 2-Spirit Youths in the Context of the COVID-19 Pandemic: Community-Based Participatory Research Study - Michael Chaiton; Rachel Thorburn; Emily Chan; Ilana Copeland; Chieng Luphuyong; Patrick Feng (JMIR Publications, 2023)
BackgroundMental health (MH) and substance use (SU) care supports are often difficult to access for the lesbian, gay, bisexual, transgender, queer, questioning, and 2-spirit (LGBTQ2S+) population. There is little known on how the shift to web-based care has affected and changed the experiences of LGBTQ2S+ youths within the MH care system. ObjectiveThis study sought to examine how web-based care modalities have affected access to care and quality of care for LGBTQ2S+ youths seeking MH and SU services. MethodsResearchers used a web-based co-design method to explore this population's relationship with MH and SU care supports, focusing on the experiences of 33 LGBTQ2S+ youths and their relationship with MH and SU supports during the COVID-19 pandemic. A participatory design research method was used to gain experiential knowledge of LGBTQ2S+ youths' lived experience with accessing MH and SU care. Thematic analysis was used to examine the resulting audio-recorded data transcripts and create themes. ResultsThemes related to web-based care included accessibility, web-based communication, provision of choice, and provider relationship and interactions. Barriers to care were identified in particular for disabled youths, rural youths, and other participants with marginalized intersecting identities. Unexpected benefits of web-based care were also found and emphasize the idea that this modality is beneficial for some LGBTQ2S+ youths. ConclusionsDuring the COVID-19 pandemic, a time where MH- and SU-related problems have increased, programs need to reevaluate current measures so that the negative effects of web-based care modalities can be reduced for this population. Implications for practice encourage service providers to be more empathetic and transparent when providing services for LGBTQ2S+ youths. It is suggested that LGBTQ2S+ care should be provided by LGBTQ2S+ folks or organizations or service providers who are trained by LGBTQ2S+ community members. Additionally, hybrid models of care should be established in the future so that LGBTQ2S+ youths have the option to access in-person services, web-based ones, or both as there can be benefits to web-based care once it has been properly developed. Implications for policy also include moving away from a traditional health care team model and developing free and lower-cost services in remote areas.